Chitosan-based films with alternative eco-friendly plasticizers: Preparation, physicochemical properties and stability. (1st February 2023) - Janik, Weronika; Ledniowska, Kerstin; Nowotarski, Michał; Kudła, Stanisław; Knapczyk-Korczak, Joanna; Stachewicz, Urszula; Nowakowska-Bogdan, Ewa; Sabura, Ewa; Nosal-Kovalenko, Hanna; Turczyn, Roman; Dudek, Gabriela
Abstract: Chitosan-based films modified with synthesized (propylene glycol monoacetate, propylene glycol esters of fatty acids, and epoxidized propylene glycol esters) and commercial eco-friendly plasticizers (epoxidized soybean oil and epoxidized palm oil) were prepared by a casting technique, with the aim to obtain environmentally friendly materials for packaging applications. To assess the applicability of alternative plasticizers, their properties were compared to the two most common plasticizers, i.e. glycerol and sorbitol. The chemical structure of newly synthesized plasticizers was verified by gas chromatography with mass detector, infrared spectroscopy and 1 H NMR; and their acid, epoxy, iodine, and saponification values were determined. Plasticized chitosan-based films were characterized in terms of hydrophilic, barrier, thermal, mechanical properties, zeta potential and morphology, confirming their flexibility and homogeneity. The research confirmed that the alternative plasticizers introduced by us are more effective than commercially available ones, exhibiting lower hydrophilicity and superior mechanical properties compared to samples plasticized with traditional plasticizers. Moreover, these properties were found to be even better after ageing for 10 months. Graphical abstract: Unlabelled Image Highlights: Plasticizers based on esters and epoxidized esters as an alternative to glycerol and sorbitol Comparison of the properties of films containing commercial plasticizers with alternative plasticizers Improved mechanical and hydrophilic properties after addition of alternative plasticizers Extension of the ageing process of the film thanks to the use of alternative plasticizers